Pewarnaan Titik pada Keluarga Graf Sentripetal - Istamala Idha Retnoningsih; Dafik Dafik; Saddam Hussen (jcgant, 2022)
The graph G is defined as a pair of sets (V,E) denoted by G=(V,E), where V is a non-empty vertex set and E is an edge set may be empty connecting a pair of vertex. Two vertices u and v in the graph G are said to be adjacent if u and v are endpoints of edge e=uv. The degree of a vertex v on the graph G is the number of vertices adjacent to the vertex v. In this study, the topic of graphs is vertex coloring will be studied. Coloring of a graph is giving color to the elements in the graph such that each adjacent element must have a different color. Vertex coloring in graph G is assigning color to each vertex on graph G such that the adjecent vertices u and v have different colors. The minimum number of colorings produced to color a vertex in a graph G is called the vertex chromatic number in a graph G denoted by χ(G).